(3aUd aj eYGfi YhGed GdEYQGHs
(3ChdgG (B:s
(3EYde Cf GdCda djfI bSeGf hgeRI aGddjfI GdJi dGjJYOG HgG dCfgG dGJbHd GdMQcI CUdkG hJSei GdMQa GdgGOi s
(3BNQgG (B:s
(3MQa GdjGA GdjGA GdeaQOI Jchf VejQkG ddeDfKI ai Jbhejf hbhei aEfg GdQMje GdQMef hgh CcQe eSFhd hCYXe eCehd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs